2019
DOI: 10.3390/fib7120100
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Temperature on the Mechanical Properties of Steel Fiber-Reinforced Concrete

Abstract: The effect of high temperature on the mechanical properties of concrete reinforced by steel fibers with various aspect ratios has been investigated in this study. Concrete specimens were fabricated from four different concrete mixtures and cured for 28 days. After curing and natural drying, the specimens were annealed at a temperature of 500 • C for 3 h in an electric furnace. The compressive and tensile strengths as well as the elastic moduli of the produced specimens were determined. It was found that the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Steel fiber is one of the most popularly used fibers to enhance the mechanical strength of concrete [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Nguyen et al indicated that the effects of rubber aggregates and fiber reinforcement could result in better cracking resistance for cement mortar [28].…”
Section: Introductionmentioning
confidence: 99%
“…Steel fiber is one of the most popularly used fibers to enhance the mechanical strength of concrete [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Nguyen et al indicated that the effects of rubber aggregates and fiber reinforcement could result in better cracking resistance for cement mortar [28].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of steel fibers with various aspect ratios on some mechanical properties of concrete was investigated after the exposure to high temperature reaching to 500 • C for 3 h in an electric furnace. It was noted that steel fiber-reinforced concrete compared to control concrete had a flexural toughness less affected by high temperature [13]. The behavior of RPC columns reinforced by fibers was studied after the exposure to fire flame for the period 2 h at one side and subjected to eccentric load.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of concrete under tension can be substantially improved by the addition of steel fibers since SFRC exhibits increased tensile strength and mainly post-peak deformation capability showing pseudo-ductile behavior due to the gradual debonding failure of the fibers [ 78 ]. Various analytical stress versus strain expressions have been proposed to simulate the SFRC tensile behavior [ 79 , 80 , 81 ]. In this study, a smeared crack model for plain concrete with tension softening that has been addressed and experimentally verified by the authors [ 82 , 83 ] is adopted.…”
Section: Methodsmentioning
confidence: 99%